Effect of Spiritual Intelligence on Emotional Intelligence of Female Undergraduate Students - Fatemeh Zare, Khatoon vakili, (Opción, 2019)
The purpose of this study was to determine the effect of spiritual intelligence on emotional intelligence in female undergraduate students of educational science and psychology of Payame Noor University of Sari. In this research, the correlation method has been used. Data were collected using the 4-scale Schutte emotional intelligence questionnaire and 4-scale spirituality questionnaire (SQ). The findings showed that spiritual intelligence does not affect emotional intelligence. In conclusion, the importance of spiritual beliefs in life has no effect on the emotional intelligence of students.